Mental health and fear of COVID-19 in Iranian pregnant women: A multi-center study - Samaneh Torkian; Fatemeh Torkian; Sahebjan Torkian; Fatemeh Mokhtari (Kashan University of Medical Sciences, 2022)
Background: The new coronavirus (COVID-19) pandemic has extensive psychological effects on pregnant women. Objectives: The aim of this study was to assess mental health, fear of COVID-19, and their association among pregnant women. Methods: This cross-sectional study was conducted on 607 pregnant women in Isfahan, Iran, from September 26 to December 20, 2020. The pregnant women were randomly selected from health centers affiliated with Isfahan University of Medical Sciences using a two-stage cluster sampling. A three-part web-based questionnaire (i.e., a demographic questionnaire, the Fear of COVID-19 Scale, and the General Health Questionnaire) was used to collect data. Chi-square test, independent-samples t-test, and logistic regression analysis were used for data analysis. Results: Most participants (73%) had a high level of fear of COVID-19, while 11% had a history of COVID-19 infection. In the final model, poor financial status (odds ratio [OR] = 3.06, 95% confidence interval [CI]: 1.32-7.10), COVID-19 infection (OR = 2.25, 95% CI: 1.22-4.16), history of mental disorders (OR = 10.11, 95% CI: 2.44-41.75), and number of pregnancies (OR = 2.59, 95% CI: 1.39-4.81) were associated with a significant increase in the chance of mental health disorder. A high COVID-19 fear score resulted in a 29% increase in mental health disorders, although this increase was not statistically significant. Conclusion: The prevalence of fear of COVID-19 was high among pregnant women. Poor financial status, number of pregnancies, history of COVID-19 infection, and a history of mental problems were associated with an increased risk of mental health disorders in pregnant women.